Longitudinal functional connectivity changes correlate with mood improvement after regular exercise in a dose‐dependent fashion. (23rd March 2016) - Tozzi, Leonardo; Carballedo, Angela; Lavelle, Grace; Doolin, Kelly; Doyle, Myles; Amico, Francesco; McCarthy, Hazel; Gormley, John; Lord, Anton; O'Keane, Veronica; Frodl, Thomas
Abstract: Exercise increases wellbeing and improves mood. It is however unclear how these mood changes relate to brain function. We conducted a randomized controlled trial investigating resting‐state modifications in healthy adults after an extended period of aerobic physical exercise and their relationship with mood improvements. We aimed to identify novel functional networks whose activity could provide a physiological counterpart to the mood‐related benefits of exercise. Thirty‐eight healthy sedentary volunteers were randomised to either the aerobic exercise group of the study or a control group. Participants in the exercise group attended aerobic sessions with a physiotherapist twice a week for 16 weeks. Resting‐state modifications using magnetic resonance imaging were assessed before and after the programme and related to mood changes. An unbiased approach using graph metrics and network‐based statistics was adopted. Exercise reduced mood disturbance and improved emotional wellbeing. It also induced a decrease in local efficiency in the parahippocampal lobe through strengthening of the functional connections from this structure to the supramarginal gyrus, precentral area, superior temporal gyrus and temporal pole. Changes in mood disturbance following exercise were correlated with those in connectivity between parahippocampal gyrus and superior temporal gyrus as well as with the amount of training. No changes were detected in the control group. In conclusion, connectivity from the parahippocampal gyrus to motor, sensory integration and mood regulation areas was strengthened through exercise. These functional changes might be related to the benefits of regular physical activity on mood. Abstract : In a randomized controlled trial conducted on 38 healthy adults, mood improvement after 16 weeks of regular physical exercise correlates with a dose‐dependent increase in functional connectivity between the parahippocampal gyrus and mood regulation areas.